ANÁLISIS SEMIÓTICO DE LOS LOGOTIPOS DE LOS MEDIOS DIGITALES INFORMATIVOS DE LA CIUDAD DE BABAHOYO - PAMELA YULIANA UCA VILLEGAS (2024)
The present research deals with the semiotic analysis of the logos of the digital news media of the city of Babahoyo, where it is highlighted that citizens have adapted to the fluidity of information through digital platforms. Furthermore, the study highlights that semiotics is responsible for unraveling the elements that make up the emblems and their meaning and that logos are the visual identification to identify in the digital information market. The objective of the research is to analyze the semiotic characteristics of the digital media logos of the city of Babahoyo. The methodology of the study is made up of a qualitative approach, and the type of research is descriptive and explanatory. The research technique is the interview which is aimed at communication professionals with experience in graphic design on the topic of logos for digital news media; C6 Televisión Babahoyo, ND Noticias, Fuente Informativo, Babahoyo Al Día and El Vocero. The investigation concluded that the logos of Babahoyo's digital news media are presented in several aspects, in these the semiotic elements that reflect the identity, and the value that each one has within the market.